2003
DOI: 10.1128/mcb.23.7.2600-2607.2003
|View full text |Cite
|
Sign up to set email alerts
|

Native Polycystin 2 Functions as a Plasma Membrane Ca2+-Permeable Cation Channel in Renal Epithelia

Abstract: Mutations in polycystin 2 (PC2), a Ca2؉ -permeable cation channel, cause autosomal dominant polycystic kidney disease. Whether PC2 functions in the endoplasmic reticulum (ER) or in the plasma membrane has been controversial. Here we generated and characterized a polyclonal antibody against PC2, determined the subcellular localization of both endogenous and transfected PC2 by immunohistochemistry and biotinylation of cell surface proteins, and assessed PC2 channel properties with electrophysiology. Endogenous P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
160
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(177 citation statements)
references
References 41 publications
16
160
1
Order By: Relevance
“…While this question has not been formally addressed, there are several lines of evidence to suggest the former. In this regard, biochemical experiments have shown that only a small fraction of transfected PKD2 (>5%) reached the plasma membrane [36], in agreement with a previous report that native or transfected PKD2 could be barely detected in the plasma membrane of LLC-PK1 cells [24]. Therefore, the modest increase in whole cell currents in the Ma et al study [36] could simply reflect low presence of PKD2 in the plasma membrane.…”
Section: Modes Of Pkd2 Activationsupporting
confidence: 90%
See 3 more Smart Citations
“…While this question has not been formally addressed, there are several lines of evidence to suggest the former. In this regard, biochemical experiments have shown that only a small fraction of transfected PKD2 (>5%) reached the plasma membrane [36], in agreement with a previous report that native or transfected PKD2 could be barely detected in the plasma membrane of LLC-PK1 cells [24]. Therefore, the modest increase in whole cell currents in the Ma et al study [36] could simply reflect low presence of PKD2 in the plasma membrane.…”
Section: Modes Of Pkd2 Activationsupporting
confidence: 90%
“…In terms of their subcellular localizations, TRP channels have been localized in various subcellular sites such as plasma membrane [12], endoplasmic reticulum [16], lysosomes [17][18][19], and primary cilium [20][21][22]. Consistently, PKD2 expression has been reported in the plasma membrane [23,24], ER [25], primary cilium [26], centrosome [27], and mitotic spindles in dividing cells [28]. Specific functions of PKD2 have been associated with its expression in the plasma membrane, ER, and primary cilium (Fig.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…PKD2 is a non selective cation channel and loss of function has been implied to cause polycystic kidney disease (Luo et al, 2003). The activity of the channel is influenced by the gene product of PKD1 which directly interacts with the C-terminal of PKD2 (Tsiokas et al, 1997;Xu et al, 2003, Vandorpe et al, 2002.…”
Section: Pathophysiological Roles Of Trp-proteinsmentioning
confidence: 99%